Synthesis and Structural Studies of 2-Phenylimino-3-aroyl/ acyl-5-aroyl/acyl hydrazino-1,3,4-thiadiazolidines and Their Acetyl Derivatives - CHOUDHARI, J.R.; BERAD, B.N. (Asian Journal of Chemistry, 2010)
Synthesis of several 2-phenylimino-3-aroyl/acyl-5-aroyl/acyl hydrazino-1,3,4-thiadiazolidines (V) have been carried out by the interaction of bis-1,5-aroyl/acyl-3-thiocarbohydrazides (II) with N-phenylisocyanodichloride (III). The product obtained (IV) on basification with dilute ammonium hydroxide afforded the free bases (V). The title compounds in 1:1 ratio gave monoacetyl derivatives (VI). The structures of all these compounds were established on the basis of elemental analysis and spectral studies.